The Use of YouTube Video as Learning Media to Improve Students' Speaking Ability - Ayrin Hairani; Neni Harahap (Indonesian Journal Publisher, 2025)
This study is to investigate whether the use of YouTube Video as Leaning Media can improve students' speaking ability. The study was conducted at SMP Muhammadiyah 57 Medan with the number of samples of 12 students from class 8-C. The method used was a quantitative design with the integration of pre-test, treatment and post-test. The instruments of data collection consisted of speaking test and rubrics, video recorder and projector in gaining data of students; speaking performance. Then the data analysed by 5 phases of: Scoring the speaking test, Calculating the average score, Measuring the improvement, comparing the result, interpreting the result. The results of this study showed that the use of YouTube Video as learning media can improve students speaking ability. Students’ speaking scores were increased after given by a treatment via a YouTube video entitled